Paediatric procedural sedation and analgesia in the emergency centre: a description of the fasting status - Dunn, Cornelle (Division of General Surgery, 2023)
Background Procedural sedation and analgesia (PSA) is considered a core competency in emergency medicine as patients present to the Emergency Centre (EC) on an unscheduled basis, often complex complaints that necessitate emergent management (1). Previous evidence has consistently shown that procedural sedation and analgesia(PSA) in the EC in the paediatric population, even the very young, is safe if appropriate monitoring is performed and appropriate medications are used (2–5). The aim of the study was to describe the indications for PSA in the paediatric EC population, the fasting status of paediatric patients undergoing PSA, and the complications observed during PSA in a single Western Cape emergency centre. Methods A retrospective, descriptive study was conducted at Mitchells Plain Hospital, a district-level hospital situated in Mitchells Plain, Cape Town. All paediatric patients younger than 13 years of age who presented to the EC and received PSA during the study period (December 2020 – April 2021) were included in the study. Data was extracted from a standardised PSA form and simple descriptive statistics were used. Results A total of 116 patients (70,7% male) were included: 13 infants (<1 year of age) 48 young children (1-5 years of age) and 55 older children (5-13 years of age). There were only 2 (1,7%) complications documented, both of which were vomiting and did not require admission. The most of patients received ketamine (93,1%). The standardised PSA form was completed in 49,1% of cases. Indications for PSA included burns debridement (11,2%), suturing (17,2%), fracture reduction (23,3%), lumbar punctures (31,9%) and others (27,6%). The indications for PSA varied between the different age groups. Conclusion The study findings are in accordance with previous international literature. Emergency Centre PSA in the paediatric populations did not show an increase in interventions or complications, despite the fasting status (6). Safe, timely PSA with minimal pain and unnecessary suffering can become the norm in Emergency Medicine practice in South Africa.